Estilos de liderança, estágios de maturidade e desenvolvimento de equipes : um estudo de caso em uma empresa do setor financeiro - Oliviera, Carlos César de (2009)
The conceptualization of work teams as groups of people with complementary skills that carry interdependent tasks out, hence sharing the responsibility for superior results for the sum of the individual performance points to the imperative of a greater collaboration among team members. The creation of synergy, as expected from the action of teams, depends on efficacious leadership, and maturity of teams. In view of this, the goal is to assess leadership styles and the degree of maturity of teams in a big financial Institution. The study counts with research of a qualitative and quantitative, exploratory nature and the conformance of the case study. Direct Observation and content analysis were used in semi-structured interviews. To rate the teams as to their maturity used the questionnaire Teams Scale of Maturity. The sample per convenience involved twenty teams with an overall of 126 participants. The identification of leadership styles in the twenty leaders used the LASI Questionnaire Style of the Superior. As a result, it was verified that thirteen out of the twenty teams studied have a high level of maturity, which were identified with the denomination of real teams, and seven showed intermediate levels of maturity. The median of studied teams (3.87) is high, thus enabling the assertion that the company has mature teams. In this sense, the research proved the presence of conditions described by Katzenback and Smith (1994) to characterize a work team. As for the leadership style it was seen that eight leaders in the teams had a style classified as E-1 Determine (high task and low relation), seven were classified as E -2 Persuade (high task and high relation), five had style E 3 Share (high relation and low task) and none showed style E 4 Delegate (low relation and low task). The study evinced the possibility to improve the choice of leader with style that is adequate for the stage of maturity of each team.